Controlled synthesis of Ag2O/g-C3N4 heterostructures using soft and hard templates for efficient and enhanced visible-light degradation of ciprofloxacin. Issue 22 (15th November 2021) - Kadi, Mohammad W.; Mohamed, Reda M.; Bahnemann, Detlef W.
Abstract: Pluronic 31R1 surfactant and MCM-41 silica were used to fabricate mesoporous Ag2 O/g-C3 N4 heterostructures with improved surface areas. The fabricated mesoporous nanocomposite was used to photo oxidize ciprofloxacin. The TEM images of Ag2 O/g-C3 N4 indicated a uniform dispersion of spherical approximately 4-nm Ag2 O nanoparticles on g-C3 N4 . The mesoporous 0.9% Ag2 O@g-C3 N4 heterostructure exhibited 100% efficiency in ciprofloxacin oxidation within 60 min when compared with the 25% efficiency in 120 min of pure mesoporous Ag2 O and 10% efficiency in 120 min of pure g-C3 N4 . The highest ciprofloxacin oxidation efficiency achieved was 100%, which was four and ten times better than those of Ag2 O and g-C3 N4, respectively. This superior performance of the mesoporous Ag2 O/g-C3 N4 was attributed to the high dispersion of nano-sized mesoporous Ag2 O particles on the g-C3 N4 surface, narrow bandgap, and significantly high surface areas. The powerful interaction between Ag2 O and g-C3 N4 ensured robust durability of Ag2 O/g-C3 N4 heterostructures, which is evident in the fact that five recycling trials of the photocatalyst rendered a minimal loss of efficiency.